Formulación de una arquitectura empresarial para la empresa provincial de vivienda - Guachamín Sosoranga, Edison Iván (2016)
Enterprise Architecture (EA), is a practice that is based on a comprehensive view of the organization, that lets align processes, organization, people, applications, information and technology infrastructure, through analyzing gaps for each domain and the projects portfolio formulation that will make possible the company is transformation. For AE development, this work has used the TOGAF framework which includes ADM methodology, this framework is supported by the best industry practices. The Empresa Provincial de Vivienda has several computer systems but those have obsolete technology, without suppliers support, isolated data sources, no integral solutions, this is a technology barrier to get real information to make management decisions. Actually, the company needs a new technological platform that supports business objectives of the company.